Untargeted flower volatilome profiling highlights differential pollinator attraction strategies in muscadine - Darwish, Ahmed G.; Das, Protiva R.; Olaoye, Eniola; Gajjar, Pranavkumar; Ismail, Ahmed; Mohamed, Ahmed G.; Tsolova, Violeta; Hassan, Nasser A.; El Kayal, Walid; Walters, Kellie J.; El-Sharkawy, Islam (Frontiers in Plant Science, 2025)
Floral aromas are a mixture of volatile organic compounds, essential attributes associated with the attraction of different pollinators. This investigation is the first in-depth exploration of the volatile profiles of sixteen muscadine grape genotypes, producing female and perfect flowers using the headspace solid-phase microextraction (HS-SPME)-GC-MS-based untargeted volatilomics approach. A total of one hundred fifty volatile metabolites were identified in the muscadine flower genotypes, including the functional groups of hydrocarbons, esters, alcohols, ketones, aldehydes, miscellaneous, and acids. Multivariate statistical analysis for volatile terpenes revealed eleven bio-marker terpene volatiles that primarily distinguish between female and perfect flowers. The β-elemene, β-bisabolene, and α-muurolene were the marker volatiles characterizing perfect flowers; however, α-selinene, (Z,E)-α-farnesene, and (E,E)-geranyl linalool were the typical marker terpene in the female flowers. Perfect flowers exhibited better pollinator attraction capacity associated with a higher number of flowers per inflorescence, enhanced pollinator rewards, and higher numbers and quantities of terpene volatiles than female flowers, resulting in superior pollinator attraction capacity and fruit set efficiency. The pollinator attraction mechanism of female flowers exhibited several morphological and biochemical floral defects, causing random pollinator visits and low fruit set efficiency. The controlled pollination assay could express female flowers’ full fruit set capabilities by avoiding casual insect pollination. This comprehensive study suggests that these marker terpenes might contribute to pollinator attraction in muscadine flower genotypes and should be considered an excellent reference for agroecosystem ecologists and entomologists.